Molecular dynamics study on fluorine radical multilayer adsorption mechanism during Si, SiO2, and Si3N4 etching processes. (21st October 2016) - Numazawa, Satoshi; Machida, Ken; Isobe, Michiro; Hamaguchi, Satoshi
Abstract: The surface adsorption processes of fluorine (F) radicals on silicon (Si), silicon dioxide (SiO2 ), and silicon nitride (Si3 N4 ) substrates during reactive ion etching (RIE) with F incident flux have been studied by molecular dynamics (MD) simulation with bond-order potential functions. In such processes, F radicals are trapped on adsorption sites and thin mixing layers are formed. The radicals break existing bonds near the surface and new trapping sites are generated with specific probabilities. By introducing an extended Langmuir adsorption model, the multilayer adsorption mechanism during etching has been elucidated. The newly proposed Langmuir model takes into account this dynamical site generation by considering two different states of the F mixing layer. The adsorption–desorption processes predicted by the extended Langmuir model are compared with MD simulation results.